Models of Code and the Digital Architecture of Time. - Johnston, Andrew R. (Discourse: Journal for Theoretical Studies in Media & Culture)
The article focuses on digital technology and problem while developing digital graphics systems. It states that laborious process of coding the digital animations was common in the style of computer usage and sharing known as batch processing. It mentions that time within systems is registered through electronic signals in megahertz frequencies and articulations of time structured limits that animators found working within or against during the early history of digital animation.